SULT, APPETIT OG MÆTHED: Mellem biologi og kultur - Kristensen, Søren Tange (Tidsskriftet Antropologi, 1998)
Søren Tange Kristensen: Hunger, Appetite and Satiety: Between Biology and Culture The number of people developing overweight and obesity is inereasing, as is the prevalence of eating disorders and weight preoccupation. These tendencies can be considered as expressing a polarisation of eating habits in modern societies, where lack of control or exaggerated Control over eating are still more common phenomena. At the same time, the tendencies may be seen as the result of a more general ambivalence in relation to food, which influences the experience of appetite and its regulating effeet on food consumption. So far, regulation of appetite has primarily been examined by nutritional scientists on a physiological level. However, the subjective experience of hunger, appetite, and satiety can also be seen as constituted and regulated on the individual and social level. The aim of the article is to show how appetite can be seen as a central research subject, both as the locus where food consumption is bodily regulated and as the nexus where biology, social rules, and cultural meanings meet and are negotiated by the individual.